The Role of the Arabic Language in Islamic Economy - Agus Arwani (ALSINATUNA, 2017)
This study aims to clarify the role of the Arabic language in Islamic Economy through a library research. It used descriptive approach combined with content analysis approach. Arabic is a compulsory language. When Islam expanded and came into contact with other civilizations, Arabic acted as a bridge of scholarship through the movement of translation. This movement got the right momentum, not only from the ulama, but also political and financial support from the umara, so the synergy of power and knowledge transformed into a powerful force in the development of Islamic science and civilization. Arabic in the future is predicted to play a more optimal role if Islamic educational institutions can synergize with power in establishing its role as a language of diplomacy, language of education, and language of communication in various fields especially in the Islamic economy field.